Advances in neuromarketing and improved understanding of consumer behaviour: analysing tool possibilities and research trends - Bhardwaj, Seema; Thapa, Surya Bahadur; Gandhi, Aradhana (Cogent business & management, 2024)
Neuromarketing, an emerging subject and generating diverse body of knowledge in the extant literature, this study aims to present qualitative and quantitative knowledge of the neuroscientific domain by analysing the application of various neuromarketing tools and techniques in conducting the research studies. This paper comprises a systematic review of 61 journal articles combined with bibliometric analysis of 577 peer-reviewed journal articles following the PRISMA framework, employing content analysis and keyword co-occurrence analysis. The comprehensive analysis presented a research profile illustrating chronological trends in neuromarketing research and discovered potential new domains, demonstrating explored and unexplored practical utility in neuromarketing. The results highlight the application of Functional Magnetic Resonance Imaging (fMRI), eye-tracking, and neural networks for data analysis as prospective areas in neuroscientific research. An overview of existing neuroscientific tools was presented based on the user context and research outcomes, outlining their benefits and limitations, along with ethical concerns. A theoretical framework was proposed to illustrate the neuromarketing effect on consumer behaviour, suggesting potential areas for future investigation. The findings of the study will be of interest to scholars and marketers in providing the insights on various neuro tools and techniques, and its significant role in decision-making, such comprehension may improve marketing effectiveness.